2009
DOI: 10.1111/j.1745-6924.2009.01164.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Is Not Always Better Than One

Abstract: Over the past two decades, there has been an upsurge in theoretical frameworks alluding to the existence of two different processing systems that supposedly operate according to different rules. This article critically examines the scientific advance offered by these theories (in particular advances in the domains of reasoning, decision making, and social cognition) and questions their theoretical coherence as well as the evidence for their existence. We scrutinize the conceptual underpinnings of two-system mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
167
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 598 publications
(172 citation statements)
references
References 98 publications
3
167
0
2
Order By: Relevance
“…Some researchers have, in contrast, argued that the evidence used to support separate systems is more consistent with a single-system account (see, e.g., Kruglanski & Gigerenzer, 2011;Osman, 2004). Keren and Schul (2009) proposed a uni-model and argued that the presence of conflict is not adequate evidence for two independent systems. They suggest that the belief-bias effect can be explained by assuming that logical validity and believability are two distinct types of external criteria that a single system can use to evaluate a conclusion, and that the level or awareness of alternative responses fluctuates continuously when one is reasoning.…”
Section: Discussionmentioning
confidence: 96%
“…Some researchers have, in contrast, argued that the evidence used to support separate systems is more consistent with a single-system account (see, e.g., Kruglanski & Gigerenzer, 2011;Osman, 2004). Keren and Schul (2009) proposed a uni-model and argued that the presence of conflict is not adequate evidence for two independent systems. They suggest that the belief-bias effect can be explained by assuming that logical validity and believability are two distinct types of external criteria that a single system can use to evaluate a conclusion, and that the level or awareness of alternative responses fluctuates continuously when one is reasoning.…”
Section: Discussionmentioning
confidence: 96%
“…The dual-mind framework received some criticism concerning the large number of postulated dualities sometimes contradicting one another (see: Keren and Schul 2009) and the multi-criteria based description of processing in each way, thus the congruency of those criteria is hard to achieve in everyday situations (Moors and De Houwer 2006). Despite this, when focusing only on the mechanisms underlying both types of processing (Strack and Deutsch 2004), and thus on similarities rather than differences between the different processes (e.g.…”
Section: Dual Mechanisms Of Processing In Emotion-cognition Relationsmentioning
confidence: 99%
“…Watson and Tellegen (1985) have presented positive affect and negative affect as two independent dimensions: high versus low positive affect and high versus low negative affect. Seeing affect as composed of two systems, each one of them categorized as high and low, leads to four different combinations beyond the two-system approach (for a point of view on two-system theories see Keren & Schul, 2009). Wilson, Gullone, and Moss (1998) have shown that there does not exist any significant correlation between the extent of positive and negative affectivity, which implies that a 'divergent validity' appears to be the case.…”
Section: Affective Statesmentioning
confidence: 99%